School space as a "safe space" and a "secured space": educational and architectural challenges - Vasojević, Nena A.; Vučetić, Ivana; Ignjatović, Suzana; Buturović, Željka (Studies in Teaching and Education, 2024)
Following the unfortunate event of school shooting in Belgrade, the dominant topic in the Serbian public, society and educational domain, in recent months, is the topic of school safety and security, i.e. safety and security in the school area. On the other hand, no relevant scientific sources regarding this phenomenon can be found in domestic literature. If we look at the relevant international publications, we come across different definitions of this term. First, this paper focuses on theoretical considerations related to the complex discourse of "safe space" and "secured space" in the educational system. Based on these considerations, it was concluded that this problem requires an interdisciplinary approach, i.e., from a cultural, psychosocial, and architectural point of view. Finally, an overview of international experience in designing safe school premises, as well as existing legal solutions for security measures in school buildings in Serbia, is given.